The Designing Motion Graphic Media to Enhance Basic English Learning on the Topic A-Z (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to design motion graphic media for English learning development at the beginner level A-Z and 2) study the satisfaction of the sample group toward motion graphic media for English learning development at the beginner level A-Z. The sample group consisted of 30 parents who had watched the motion graphic media to promote English learning at the beginner level A-Z. The research instruments were motion graphic media for English learning development at the beginner level A-Z and an online questionnaire on the viewer’s satisfaction with the motion graphic media. The statistics used in this research were mean (x ̅), percentage, and standard deviation (S.D.) with a 5-point scale. The research results found that 1) the motion graphic media for English learning development at the beginner level A-Z had the following steps: planning, design, and development. And the evaluation process 2) Motion graphic media for motion graphic media for developing English learning at the beginning level A-Z has the evaluation result of satisfaction of content experts towards motion graphic media for developing English learning at the beginning level A-Z at a good level (x ̅ = 4.25, S.D. = 0.70). Satisfaction of experts in designing motion graphic media for developing English learning at the beginning level A-Z (x ̅ = 4.50, S.D. = 0.61). Satisfaction of the sample group towards motion graphic media for developing English learning at the beginning level A-Z (x ̅= 4.59, S.D. = 0.73)